Constraint satisfaction and optimization for space station short-term mission planning based on an iterative conflict-repair method. Issue 10 (2nd October 2016) - Bu, Hui-Jiao; Zhang, Jin; Luo, Ya-Zhong
Abstract : This article studies the optimization of space station short-term mission planning (STMP) problems. The domain knowledge including description and the concept definitions of the STMP problem are presented, an STMP constraint satisfaction model is developed, and then an iterative conflict-repair method with the resolving strategies is proposed to satisfy complicated constraints. A genetic algorithm (GA) is adopted to optimize the STMP problem. The proposed approach is evaluated using a test case with 15 missions, 13 devices and three astronauts. The results show that the established STMP constraint satisfaction model is effective, and the iterative conflict-repair method can make the plan satisfy all constraints considered and can effectively improve the optimization performance of the GA.